Application of In-Fusion™ cloning for the parallel construction of E. coli expression vectors - Bird, L; Rada, H; Flanagan, J; Diprose, J; Gilbert, R; Owens, R (Humana Press Inc., 2014)
In-Fusion™ cloning is a fl exible DNA ligase-independent cloning technology that has wide-ranging uses in molecular biology. In this chapter we describe the protocols used in the OPPF-UK to design and construct expression vectors using In-Fusion™. Our method for small scale expression screening in Escherichia coli of constructs generated by In-Fusion™ is also outlined. © Springer Science+Business Media New York 2014.